2016
DOI: 10.1007/s11906-015-0618-1
|View full text |Cite
|
Sign up to set email alerts
|

Hypertension and Stroke in Patients with Left Ventricular Assist Devices (LVADs)

Abstract: Stroke is one of the most dreaded complications of left ventricular assist device therapy in patients with end-stage congestive heart failure. There is strong evidence linking anticoagulation and infection with ischemic and hemorrhagic strokes, though recent data has emerged regarding the importance of elevated blood pressure. In the recently completed Heartware Ventricular Assist Device studies, a mean arterial pressure greater than 90 mmHg was associated with greater stroke risk, particularly the hemorrhagic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
26
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(27 citation statements)
references
References 34 publications
(45 reference statements)
1
26
0
Order By: Relevance
“…Neurologic events remain the most devastating complications of LVAD support 12,15, 1821 ; thus, despite advancements in LVAD technology and anti-coagulation therapy, it is imperative to examine the thrombogenicity of VAD configurations. As blood flow in the outflow graft and great vessels is characterized by high Reynolds, O(1000), and Womersley, O(10), numbers, the nuances of surgical implantation configuration may impact hemodynamic patterns, which in turn determine stress levels on endothelial and blood-suspended cells.…”
Section: Introductionmentioning
confidence: 99%
“…Neurologic events remain the most devastating complications of LVAD support 12,15, 1821 ; thus, despite advancements in LVAD technology and anti-coagulation therapy, it is imperative to examine the thrombogenicity of VAD configurations. As blood flow in the outflow graft and great vessels is characterized by high Reynolds, O(1000), and Womersley, O(10), numbers, the nuances of surgical implantation configuration may impact hemodynamic patterns, which in turn determine stress levels on endothelial and blood-suspended cells.…”
Section: Introductionmentioning
confidence: 99%
“…13 It is also possible that previously existing chronic hypertension can be exacerbated after LVAD implantation if the blood pressure in patients on LVADs is not actively maintained at lower levels. 14 Studies have shown that MAPs over 100 mm Hg during the 48 h prior to hospital discharge are associated with a higher incidence of subsequent ischemic and hemorrhagic strokes 16 months after LVAD implantation ( Figure 1). 15 Following the original ENDURANCE and Supplemental ENDUR-ANCE trials, Cho and associates published a meta-analysis of 48 studies (11 310 patients) documenting the stroke rates in HeartMate II and HeartWare recipients.…”
Section: Stroke Risk In Axial and Radial Continuous-flow Vadsmentioning
confidence: 99%
“…Other observational studies in recent years have yielded mixed overall results as well. 14,[17][18][19][20][21][22] Most recently, Bishawi et al showed a significant decrease in cerebrovascular accidents (CVAs) with centrifugal pumps (23% vs 77%). 3 (Figure 2).…”
Section: Stroke Risk In Axial and Radial Continuous-flow Vadsmentioning
confidence: 99%
See 2 more Smart Citations